2020
DOI: 10.1101/2020.07.08.193714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the small chromosomalPrionium serratum(Cyperid) demonstrates the importance of a reliable method to differentiate between mono- and holocentricity

Abstract: For a long time, the Cyperid clade (Thurniceae-Juncaceae-Cyperaceae) was considered as a group of species possessing holocentromeres exclusively. The basal phylogenetic position of Prionium serratum L. f. Drège (Thurniceae) within Cyperids makes this species an important specimen to understand the centromere evolution within this clade. Unlike expected, the chromosomal distribution of the centromere-specific histone H3 (CENH3), alpha-tubulin and different centromere associated post-translational histon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…(2019) reported that Juncus L., a genus regarded as exclusively holocentric, contains monocentric species. Also recently it was reported that Prionium serratum (Thurniaceae) is also monocentric ( Baez et al, 2020 ). More detailed work in this area is needed to provide insights into the evolution of holocentric chromosomes in Cyperales, such as whether it arose independently in each of the major clades.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) reported that Juncus L., a genus regarded as exclusively holocentric, contains monocentric species. Also recently it was reported that Prionium serratum (Thurniaceae) is also monocentric ( Baez et al, 2020 ). More detailed work in this area is needed to provide insights into the evolution of holocentric chromosomes in Cyperales, such as whether it arose independently in each of the major clades.…”
Section: Introductionmentioning
confidence: 99%